1980
DOI: 10.1111/j.1365-2141.1980.tb07167.x
|View full text |Cite
|
Sign up to set email alerts
|

Acidified Glycerol Lysis Test: a Screening Test for Spherocytosis

Abstract: Acidified glycerol lysis test (AGLT) is a screening procedure which has been developed for spherocytosis. AGLT was found positive in 100% of 48 patients suffering from hereditary spherocytosis, 100% of nine couples of affected parents, and 86% of 14 couples of clinically healthy parents. The test was positive in acquired spherocytosis and negative in normal controls. AGLT appears to have a predictive value higher than the entire battery of conventional tests. It is simple, rapid, inexpensive, gives clear-cut r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0
4

Year Published

1985
1985
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 0 publications
3
58
0
4
Order By: Relevance
“…These tests, which are known to have different sensitivities, 25 have been mostly used individually, 6,15,43 and their performance has never been related to the defective protein. Our results confirmed that the sensitivity of these tests varies greatly 30 and showed that it was independent of the cytoskeletal abnormality and of the extent of the protein deficiency. We also demonstrated that, among the traditional screening tests for HS, the acidified glycerol lysis test had the highest sensitivity, even higher than that reported for the flow cytometric eosin-5-maleimide binding test, 33 recently recommended by the General Haematology Task Force of the British Committee for Standards in Haematology.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…These tests, which are known to have different sensitivities, 25 have been mostly used individually, 6,15,43 and their performance has never been related to the defective protein. Our results confirmed that the sensitivity of these tests varies greatly 30 and showed that it was independent of the cytoskeletal abnormality and of the extent of the protein deficiency. We also demonstrated that, among the traditional screening tests for HS, the acidified glycerol lysis test had the highest sensitivity, even higher than that reported for the flow cytometric eosin-5-maleimide binding test, 33 recently recommended by the General Haematology Task Force of the British Committee for Standards in Haematology.…”
Section: Discussionsupporting
confidence: 78%
“…The reference values for adults in our hospital were 26 : Hb 12.2-15.1 g/dL for females, 13.6-16.0 g/dL for males; mean corpuscular volume (MCV) 81-98 fL; mean cell hemoglobin content (MCHC) 31-36 g/dL; reticulocyte count 24-84×10 9 /L; reference values for children were obtained from Nathan et al 27 Bilirubin, serum iron, total iron binding capacity, and ferritin were determined using Integra 800 (Roche, Mannheim, Germany) (reference values: unconjugated bilirubin <12.8 IU, transferrin saturation 16-54%, serum ferritin 15-355 ng/mL).The number of spherocytes in peripheral blood was assessed indepently by two experts. For each patient, red cell osmotic fragility was evaluated by performing the following tests: NaCl osmotic fragility test on both fresh and incubated blood, 28 the standard glycerol lysis test, 29 the acidified glycerol lysis test 30 and the pink test. 31 The reference group consisted of 274 healthy blood donors giving blood for the first time; 30 moreover, since one normal sample (from a healthy donor) was always run together with samples from patients, the baseline reference values were periodically updated.…”
Section: Hematologic Assays and Iron Status Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The acid glycerol lysis test has a higher detection rate in asymptomatic relatives of known affected individuals than has the osmotic fragility test. 20 Osmotic gradient ektacytometry 21 and eosin-5-maleimide (EMA) binding tests 22 have a higher predictive value in diagnosing HS because there are no reports of positive results in immune or non-membrane-associated disorders. Mariani et al performed different tests to evaluate osmotic fragility and established that the association of the acid glycerol lysis test and the NaCl test on incubated blood reached a sensitivity of 99%, even considering patients with atypical disease.…”
Section: Diagnosismentioning
confidence: 99%
“…As these tests do not have a high degree of sensitivity and specificity, milder and atypical cases of HS may be missed (4,5). The confirmation of diagnosis requires sodium dodecyl sulfate polyacylamide gel electrophoresis (SDS-PAGE) analysis of red cell membrane proteins to identify the specific protein deficiency (6), although this is not routinely done in most hematology laboratories.…”
mentioning
confidence: 99%